Meta-Analisis Pengaruh Model-Model Pembelajaran Daring Terhadap Hasil Belajar Siswa - Tita Yunia Zalni (Symbiotic: Journal of Biological Education and Science, 2022)
The problems that occur today have a great effect on the whole world. All activities that normally can be carried out smoothly have been hampered due to the Covid-19 pandemic, one of which is the education sector, including the impact of this pandemic. The purpose of this study was to analyze the learning strategies used by teachers during covid-19 on student learning outcomes. This research method is a meta-analysis technique that summarizes several research results, analyzes, reviews, data from several previous studies originating from the national journal published (2016-2021), and the type of this research is qualitative research. The purpose of this meta-analysis is to determine the effect of bold learning models on student learning outcomes. From this research, it can be seen that there are differences in the learning strategies carried out by each journal. Therefore, there is a need for a good and directed learning strategy for the learning process during this COVID-19 pandemic. In the results of research on the effect of the learning model when daring on student learning outcomes, the effect size value is 0.614 with a medium category.